Study of Beta 2-Adrenergic Receptor Polymorphisms among Hypertensives - Atia, Ahmad Elbadry; Ku Zaifah, Norsidah; Abdullah, Nor Zamzila; Mokhtaar, Rafidah Hanim; Md Aris, Mohd Aznan; Draman, Samsul; A.Talib, Norlelawati (2010)
Aims: The Arg16Gly and the Gln27Glu polymorphisms in the gene for the beta2-adrenergic receptor (beta2AR) have been linked to the hypertensive status. The aim of the present study was to assess the association between ;22AR polymorphisms and hypertension. Methods: In case control study, 100 unrelated patients (50 hypertensive and 50 matched controls) were analyzed for the Arg16Gly and the Gln27Glu polymorphisms by restriction fragment length polymorphism- polymerase chain reaction assay analysis. Results: The genotypes frequencies of the genotypes of the 100 individuals enrolled in the study were: Arg16 (24%); Arg16Gly (45%); Gly16 (31%); Gln27 (83%); Gln27Glu (15%), and Glu27 (2%). The present study found no association between the 2 SNPs, Arg16Gly and Gln27Glu of beta2 adrenergic receptor gene with either hypertensive status or elevated blood pressure. (P value is 0.78 (odds ratio=0.81) and 0.37 (odds ratio=1.81) for Agr16Gly, Gln27Glu respectively). Conclusion: these finding suggest that B2AR SNPs tested are unlikely to confer genetic susceptibility for hypertension status in our population samples